Low complexity acquisition algorithm for GPS signals with low SNR and high dynamic - Zhu-lin XIONG; Ce-lun LIU; Jian-ping AN; Ze-bin XIE (Tongxin xuebao)
A frequency-domain segmental shift average periodogram acquisition algorithm for GPS signals with low SNR and high dynamic was proposed. First, the parallel rough compensation of Doppler frequency rate and C/A code phase as well as segmental FFT was applied with the received signal. Second, the compensation interval was extended to precise estimation interval based on the number of data segments. Third, the branch with the nearest compensation value was chosen as the estimation branch of each estimation value and the difference of two values was reduced by segmental fre-quency spectrum shift. The correlation value of each estimation branch was obtained by non-coherent accumulation of all shifted frequency spectrums. Last, the maximum correlation value was sent to a constant false alarm rate detector to de-termine whether the acquisition was success. The results show that compared with the traditional periodogram algorithm, the proposed algorithm has much lower computational complexity and a little performance loss.